2022
DOI: 10.1037/ccp0000764
|View full text |Cite
|
Sign up to set email alerts
|

Criminal offense charges in women: A 10-year follow-up of an RCT of treatment foster care Oregon.

Abstract: Objective: The prevention of delinquency can have long-term benefits for both the individual and society. Previous work has demonstrated positive effects of Treatment Foster Care Oregon (TFCO) on reducing delinquency across a 2-year period for adolescent females involved in the juvenile justice system. The present study examined whether the effects of TFCO are present across a 10-year period, and whether criminal offenses accrued in the juvenile justice system mediate the association between intervention condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…The original study gathered residential history information (self-reported) from all participants, and then attempted to collect criminal record data from every county in which the participant lived for the duration of the study. We produced a complete record of each participant’s official criminal records by compiling the offenses at each assessment ( Leve et al, 2022 ). We then removed any duplicate offenses that occurred because of the record compilation process.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The original study gathered residential history information (self-reported) from all participants, and then attempted to collect criminal record data from every county in which the participant lived for the duration of the study. We produced a complete record of each participant’s official criminal records by compiling the offenses at each assessment ( Leve et al, 2022 ). We then removed any duplicate offenses that occurred because of the record compilation process.…”
Section: Methodsmentioning
confidence: 99%
“…Arrests and offenses Age at first arrest and frequency counts of offenses, arrests, were all measured prior to age eighteen and are based on official records. Offenses include all types (i.e., status, misdemeanors, felonies) and are nested in arrests as youth can be charged with multiple offenses at one time of arrest (Chamberlain et al, 2007;Leve et al, 2022). Days in locked settings was based on participant self-report.…”
Section: Measures Youth Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Age at first arrest and frequency counts of offenses, arrests, are all measured prior to age eighteen and are based on official records. Offenses include all types (i.e., status, misdemeanors, felonies) and are nested in arrests as youth can be charged with multiple offenses at one time of arrest (Chamberlain et al, 2007;Leve et al, 2022). Days in locked settings was based on participant self-report.…”
Section: Youth Variablesmentioning
confidence: 99%